Competition as an ambiguous discovery procedure: A reappraisal of Hayek's epistemic market liberalism - Ulrich Witt (Max Planck Institute of Economics, 2011)
Epistemic arguments play a significant role in Hayek's defense of market liberalism. His claim that market competition is a discovery procedure that serves the common good is a case in point. The hypothesis of the markets' efficient use of existing knowledge is supplemented by the idea that markets are also most effectively creating new knowledge. However, in his assessment Hayek neglects the role of new technological knowledge. He ignores that the discovery procedure induces not only price and cost competition but also competition by innovations. Thence he overlooks the ambiguity that follows from the unpredictability of the consequences of innovations. This fact is shown to challenge the epistemic foundations and the stringency of Hayek's version of market liberalism.
urn:nbn:de:gbv:27-20110630-115310-2
Keywords: B25; D80; O33; P16; Q55; 330; competition; innovation; liberalism; knowledge; self-organization; Hayek; Wettbewerb; Marktmechanismus; Wirtschaftsliberalismus; Innovation; Theorie